Питомник: роман в 3 книгах (Полина Дашкова) - Дашкова Полина Викторовна (Детектив, 2004)
Экземпляры: Ф. 10 (20020607) / Инвентарный номер: 49235 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6